Novšie trendy empirického výskumu v psychológii náboženstva = Recent trends of the empirical research in the psychology of religion - Stríženec, Michal (Religio, 1995)
Psychology of religion, as an applied psychological specialization, studies psychological rules of behavior and experience of people who believe in the existence and influence of God or other supernatural powers. Religiosity is studied by means of the same methods as other psychological phenomena, but they cannot reveal its transcendental direction. -- The article deals with the main areas of contemporary psychological research of religion. It focuses on psychodynamics of religion, religious development, conversion, religious orientation (internal, external, searching), religious dimensions, personality aspects of religiosity (sources of religious needs, images of God), coping with demanding situations and religiosity (e.g. fear of death), religiosity and criminality, etc. New methods of empirical research are considered from the point of view of their possible applications in our conditions.